EFFECT OF TUNNEL CONSTRUCTION TECHNIQUES, GROUND PROPERTIES AND TUNNEL GEOMETRICAL TO THE AMOUNT OF VOLUME LOSS (Malaysian Journal of Civil Engineering, 2018)
Ground deformation and settlement caused by underground construction and tunneling works are inevitably avoided. Nevertheless, the impact of it can always be minimized and improvised by investigating amount of volume loss occurred from past historic data. This paper explores the amount of volume loss, in relates with tunneling techniques, ground properties as well as tunnel geometry. Early study explained two phases of volume loss, which are immediate ground loss during tunneling and long term volume loss occurred over the time. Preceding research conducts to identify the range of volume loss, in percentage. As the range of proposed volume loss is not self-dependent, therefore, it is deemed important to understand and investigate the volume loss with close proximate to the local geological property and tunneling techniques. This paper concluded that there are significant impact of tunnel construction techniques, ground properties and tunnel geometric to the percentage of volume loss. With this, the outcome and recommendation of the study will provide future direction for further comprehensive and better justification for ground settlement analysis occurred, during tunnel excavation.